Technical note: What does the Standardized Streamflow Index actually reflect? Insights and implications for hydrological drought analysis - F. Lema; P. A. Mendoza; P. A. Mendoza; N. A. Vásquez; N. Mizukami; M. Zambrano-Bigiarini; M. Zambrano-Bigiarini; X. Vargas (Hydrology and Earth System Sciences)
Hydrological drought is one of the main hydroclimatic hazards worldwide, affecting water availability, ecosystems, and socioeconomic activities. This phenomenon is commonly characterized by the Standardized Streamflow Index (SSI), which is widely used because of its straightforward formulation and calculation. Nevertheless, there is limited understanding of what the SSI actually reveals about how climate anomalies propagate through the terrestrial water cycle. To find possible explanations, we implemented the Structure for Unifying Multiple Modeling Alternatives (SUMMA) coupled with the mizuRoute routing model in six hydroclimatically different case study basins located on the western slopes of the extratropical Andes and examined correlations between the SSI (computed from the models for 1-, 3-, and 6-month timescales) and potential explanatory variables – including precipitation and simulated catchment-scale storages – aggregated at different timescales. Additionally, we analyzed the impacts of adopting commonly used timescales on propagation analyses of specific drought events – from meteorological to soil moisture and hydrological drought – with focus on their duration and intensity. The results reveal that the choice of timescale for the SSI has larger effects on correlations with explanatory variables in rainfall-dominated regimes compared to snowmelt-driven basins, especially when simulated fluxes and storages are aggregated to timescales longer than 9 months. In all the basins analyzed, the strongest relationships (Spearman rank correlation values over 0.7) were obtained when using 6-month timescales to compute the SSI and 9–12 months to compute the explanatory variables, excepting aquifer storage in snowmelt-driven basins. Finally, the results show that the trajectories of drought propagation obtained with the Standardized Precipitation Index (SPI), the Standardized Soil Moisture Index (SSMI), and the SSI may change drastically with the selection of timescale. Overall, this study highlights the need for caution when selecting standardized drought indices and associated timescales, since their choice impacts event characterizations, monitoring, and propagation analyses.